Estrategias del docente y su relación con el desarrollo de la autonomía de los niños/as de 2 y 3 años de la I.E.I.P Chiquilandia - Cabrejos Alvarado, Mery (2015)
This research: Strategies of teaching and theír relationship to the development of autonomy in chíldren 2 and 3 years of age lnitial Prívate Educational lnstitution "Chiquilandía" city of Rioja, 2013, aims to determine the relationship between teaching strategies with the development of the autonomy of children aged 2 and 3 years old lnitial Prívate Educational lnstitution "Chiquílandia" Rioja city, 2013.Los year specific objectives were to describe teaching strategies of lnitial Prívate Educational lnstitution "Chiquilandia", describing the development of the autonomy of children 2 and 3 years old, and establish the relationship between teaching strategies with the development of the autonomy of children 2 and 3 years old. Strategíes of teaching is based on the theoretical assumptions of Lopez (2009), Díaz Hernández (1999), D. Vicente, M. Polanco (2008), Benitez (2009) and R. Toribio Perez (1988); and autonomy in the Ministry of Education (2013), Hebe (2010), Fernandez (2013), which exposed the importance of autonomy for the development of competencies, skills and socio-emotional development of children. They give us sufficient theoretical tools to pose the following hypothesis: There is significant relationship between teaching strategies with the development of the autonomy of children aged 2 and 3 years old lnitial Prívate Educationallnstitution "Chiquilandia" the city of Rioja, 2013. Methodologically, the research design was descriptive-correlational study, with a sample of 20 children of lnitial Prívate Educational lnstitution "Chíquilandia" and in the process of statistical analysis it was found that the central or research hypothesis is accepted with a confidence of 95 %, the same as is evídent in the graph of the Gauss curve and the value obtained from the Pearson correlation coefficient r s = O, 7915 to be a positive correlation.